Pregnancy outcome, thyroid dysfunction and fetal goitre after in utero exposure to propylthiouracil: a controlled cohort study - Rosenfeld, Hila; Ornoy, Asher; Shechtman, Svetlana; Diav‐Citrin, Orna (British journal of clinical pharmacology, 2009)
WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT • Human pregnancy experience with propylthiouracil has not shown an increased risk of major anomalies, but its use in pregnancy has been associated with fetal or neonatal thyroid dysfunction with or without goitre. • The rate of these complications has not been prospectively evaluated. WHAT THIS PAPER ADDS • Based on prospective data from the Israeli Teratology Information Service, propylthiouracil was not associated with an increased teratogenic risk. • Hypothyroidism was found in 9.5% (56.8% of whom with goitre) of fetuses or neonates, whereas hyperthyroidism was detected in 10.3%. • In most cases neonatal thyroid functions normalized without treatment. AIMS Propylthiouracil (PTU) is presently considered to be the treatment of choice for hyperthyroidism in pregnancy. It is known to cross the human placenta, and therefore may affect the fetus. The major aims of this study were to evaluate the rate of major anomalies and to report the rate of fetal goitre, accompanied by hypothyroidism, in fetuses/ newborns of mothers after in utero exposure to PTU. METHODS Prospective observational controlled cohort study of PTU‐exposed pregnancies of women counselled by the Israeli Teratology Information Service between the years 1994 and 2004 compared with women exposed to nonteratogens. RESULTS We followed up 115 PTU‐exposed pregnancies and 1141 controls. The rate of major anomalies was comparable between the groups [PTU 1/80 (1.3%), control 34/1066 (3.2%), P= 0.507]. Hypothyroidism was found in 9.5% of fetuses/neonates (56.8% of whom with goitre). Hyperthyroidism, possibly resulting from maternal disease, was found in 10.3%. Goitres prenatally diagnosed by ultrasound were successfully treated in utero by maternal dose adjustment. In most cases neonatal thyroid functions normalized during the first month of life without any treatment. Median neonatal birth weight was lower [PTU 3145 g (2655–3537) vs. control 3300 g (2968–3600), P= 0.018]. CONCLUSIONS PTU does not seem to be a major human teratogen. However, it could cause fetal/neonatal hypothyroidism with or without goitre. Fetal thyroid size monitoring and neonatal thyroid function tests are important for appropriate prevention and treatment.